2020
DOI: 10.1088/1755-1315/474/5/052053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xihuang Pill on microcirculation in DMBA combined estrogen and progesterone induced breast precancerous lesions rats

Abstract: Objective: To observe the effect of Xihuang Pill on microcirculation in 7,12-dimethylbenzoanthracene (DMBA) combined estrogen and progesterone induced breast precancerous lesions rats. Method: DMBA combined estrogen and progesterone were used to establish the model of breast precancerous lesions for 10 weeks in SD rats, then the low, medium and high dose Xihuang Pill (0.27, 0.55, 1.37g·kg−1) was given intragastric administration, and tamoxifen (4 mg·kg−1) was given intragastric administration as a positive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Its mechanisms might be associated with regulating the protein and gene expression of Cyclin A, CDK2, Bcl-2, Bax, mTOR and VEGF [8,19,20]. Based on our research [8][9][10]17], we hypothesized that XHP pharmacological mechanism for inhibiting the development of breast precancerous lesions could be closely interrelated to the PI3K/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its mechanisms might be associated with regulating the protein and gene expression of Cyclin A, CDK2, Bcl-2, Bax, mTOR and VEGF [8,19,20]. Based on our research [8][9][10]17], we hypothesized that XHP pharmacological mechanism for inhibiting the development of breast precancerous lesions could be closely interrelated to the PI3K/Akt/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We have established the rat model of breast precancerous lesion as previously reported on the literature [9][10][11]. On the 1st day, DMBA dissolved in sesame oil was given to rats by gavage at the ratio of 1 ml•100g − 1 .…”
Section: Animal Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We established a rat model of precancerous breast lesions as previously reported in the literature [9][10][11].…”
Section: Animal Model Establishmentmentioning
confidence: 99%
“…It is a classic prescription for breast precancerous lesions and prophylaxis and treatment of breast cancer, with definite clinical effects. 9,10 Our previous studies have shown that, [11][12][13] XHP can inhibit the activity of MCF-10AT cells in precancerous breast lesions and induce apoptosis by inhibiting the expression of mTOR and VEGF in PI3K/ AKT/mTOR signaling pathway, and improve the microcirculation and hemorheology of breast precancerous lesions induced by 7,12-dimethylbenzanthracene (DMBA) combined with estrogen and progesterone. Modern studies have shown that immune function status corresponds to the occurrence and progression of breast cancer, and cellular immunity plays an essential part of anti-breast cancer immunity.…”
Section: Introductionmentioning
confidence: 99%